MELESTARIKAN BUDAYA LITERASI MEMBACA PADA ANAK-ANAK USIA SEKOLAH DI DESA LAWEWE, LUWU UTARA - Maria Yessica Halik; Gracesy Prisela Christy; Maiercherinra Daud (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Reading socialization in fostering a culture of literacy in children is carried out as part of community service. This activity was carried out to raise awareness of the importance of reading in building a literacy culture in children. The increasingly rapid development of technology by presenting features that pamper its users encourages children and teenagers to prefer opening social media rather than reading books. The aim of this activity is to; (i) increasing awareness of the importance of instilling the habit of reading books as a means of improving personal quality, (ii) educating the public about the importance of enjoyable learning activities in order to optimize the child's growth and development process, and (iii) providing a comfortable reading place for the community